Compendium of Near-Wall Interaction Problem And Boundary Conditions on Smooth Solid Boundaries in Dynamics Problems of Continuous Fluid Media (Global Journal of Science Frontier Research, 2019)
Abstract not found
Keywords: continuous fluid media; dynamics; contact surfaces; wall laws; adhesion